Kiai's Strategy In Developing Student Leadership - Arifah, Siti; Ahwa, Fajar (YPI Ulul Albab, 2024)
The spirit of leadership is a character that must be possessed by students (santri) to bring about change. Leadership spirit is one of the important things to improve the quality of students in Islamic boarding schools. Therefore, it is necessary to implement a good strategy through the formulation, implementation and evaluation by the kiai as the leader. The purpose of writing this article is to describe the formulation, implementation, and evaluation of Kiai Haji Taufiqurrohman Muzakki Syah's strategy in developing the leadership spirit of female students at Pondok Pesantren Al-Qodiri 1 Jember. This study uses a qualitative method with the type of narrative research. The results of this study are: 1) Kiai Haji Taufiqurrahman Muzakki Syah's strategy formulation is carried out by formulating the vision, mission and goals as well as identifying SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) to determine the strengths and weaknesses of Islamic boarding schools and prepare institutions to face opportunities and existing threats; 2) The implementation of Kiai Haji Taufiqurrahman Muzakki Syah's strategy is carried out by analyzing strategy options as well as determining and implementing program activities, namely: leadership training, tahlil and istighosah, madrasah diniyah and Al-Qur'an education, and manaqib Syeh Abdul Qodir Al Jaelani; 3) Evaluation of Kiai Haji Taufiqurrahman Muzakki Syah's strategy was carried out by measuring and analyzing performance through evaluation meetings to prepare alternative strategies as a form of improvement.